An outbreak of swimming-pool related respiratory symptoms: An elusive source of trichloramine in a municipal indoor swimming pool - Seys, Sven F.; Feyen, Ludo; Keirsbilck, Stephan; Adams, Els; Dupont, Lieven J.; Nemery, Benoit (International journal of hygiene and environmental health, 2015)
Several members of a swimming club complained of respiratory symptoms associated with attending a municipal indoor swimming pool. Trichloramine, a volatile chlorination by-product and a potent respiratory irritant, was the most probable culprit, but the exact cause for its presence in excessive concentrations remained elusive. Twenty-two competitive swimmers and six coaches were evaluated during the outbreak and nine swimmers and four coaches were re-evaluated one year later. Symptoms were recorded by non-standardized history taking; pulmonary function testing included spirometry, measurement of fraction of exhaled nitric oxide (FENO) and histamine provocation. Concentrations of trichloramine in air were measured repeatedly by the method of Héry. The most commonly reported symptoms consisted of cough (n=16), dyspnoea (n=13), tearing eyes (n=10) and blocked or runny nose (n=6). Mean FEV1% predicted was 109.1%. Mean FENO level was 19.7 ppb (higher than 25 ppb in 3 subjects). Airway hyperreactivity to histamine (PC20≤8mg/ml) was detected in 22/26 subjects. Measured trichloramine concentrations in air exceeded the maximal concentration (WHO) of 0.5mg/m3 four times between May and October 2011 and four times between January and March 2012. Polyamine compounds, present in glue used for repairing pipework, were identified as a probable external source of nitrogen resulting in increasing trichloramine concentrations. After the removal of the presumed cause of the excessive trichloramine concentrations, most subjects improved clinically, but several subjects remained symptomatic and had bronchial hyperreactivity. A high prevalence of airway hyperreactivity, accompanied by symptoms of upper and lower airways, was detected in swimmers who had been repeatedly exposed to high trichloramine concentrations. A glue containing polyamines, used to repair a pipework, was suspected to be the source of this excessive production of trichloramine.